WEB APPLICATION SERVICE AS INFORMATION MEDIA OF MARINE TOURISM IN MORO SUB-DISTRICT (Information Technology and Telematics, 2015)
Abstract—Moro sub-district is one of many sub-districts located in Riau island, Karimun regency which has small islands that their natural resources can be used for economic needs and Marine tourism which are rarely visited by tourists. This web application service, hopefully gives information of Marine tourism in Moro sub-district that has the potential as tourism area which can be developed by the government.  However, the role of government and society are needed.  This Marine tourism application is made to help introducing tourist attractions inside Moro sub-district, and tourist (user) will also get information related to the tourist attractions, and another location such as, restaurant, worship places, lodgings, etc, to help tourist (user) who wants to visit Moro sub-district.